Defining Service Learning in Nursing Education: An Integrative Review - Neti Juniarti; Lana Zannettino; Jeffrey Fuller; Julian Grant (Jurnal Keperawatan Padjadjaran, 2016)
Despite the wide use of service learning, there is lack of a standardised definition and measurable outcomes. Definitions of service learning found in the literature vary from the very broad to the highly specific. The aim of this review was to generate a functional definition of service learning and identify its components to constructively design and evaluate service-learning approaches in nursing education. An integrative review of scholarly literature was conducted to enable a concept analysis. A comprehensive database search using the search terms through a range of electronic databases, including CINAHL, MEDLINE, ERIC, Scopus, and the Web of Science from the earliest retrievable records of each database to June 23, 2015. The search terms used in this review were nursing students, nursing education, nursing school, community health nursing, community mental health nursing, health education, and service learning or community based education. A total of 42 studies were included in the review. A functional definition of service learning is proposed and four components of service learning were identified in this review, namely a structured form of intra-curricular experiential learning, reflection, reciprocity, and setting specific outcomes and benefits for stakeholders. The proposed conceptual model of service learning could contribute to consistent development, implementation, and evaluation of service learning in nursing education. Keywords:Components, definition, nursing education, service learning. Mendefinisikan Metode Belajar Service Learningdalam Pendidikan Keperawatan: Sebuah Kajian IntegratifAbstrakMetode service learning telah banyak digunakan di institusi pendidikan keperawatan di dunia, tetapi tidak ada definisi standar dan hasil yang terukur dari metode ini. Definisi service learning yang ada saat ini sangat bervariasi mulai dari yang sangat umum sampai sangat spesifik. Tinjauan literature ini bertujuan untuk menyusun definisi fungsional dari metode service learning dan mengidentifikasi komponennya sehingga dapat digunakan untuk merancang dan mengevaluasi metode service learning dalam pendidikan keperawatan. Integrative review (tinjauan pustaka terintegrasi) dilakukan untuk melakukan analisis konsep service learning. Pencarian literature secara komprehensif melalui database elektronik yang terdiri dari CINAHL, MEDLINE, ERIC, Scopus, dan the Web of Sciencedari publikasi yang paling awal sampai dengan tanggal 23 Juni 2015. Kata kunci yang digunakan adalah: nursing students, nursing education, nursing school, community health nursing, community mental health nursing, health education, and service learning or community based education.Total 42 artikel penelitian dimasukkan dalam analisis. Definisi fungsional service learning telah disusun dan empat komponen utama service learning telah diidentifikasi yang terdiri dari pengalaman belajar lapangan intra-kurikuler yang terstruktur, refleksi, reciprocity (manfaat timbal balik), dan penentuan hasil dan manfaat yang spesifik untuk semua pihak yang terlibat. Model konseptual yang disusun dapat berkontribusi bagi institusi pendidikan keperawatan untuk mengembangkan, melaksanakan dan mengevaluasi kegiatan service learning. Kata kunci : Definisi, komponen, pendidikan keperawatan, service learning